The Impact of Village Fund Program on Improving Well-being - Joetarto, Bagoes; Setiawan, Agung; Farida, Farida (JEJAK: Jurnal Ekonomi dan Kebijakan, 2020)
Laws no. 6 of 2014 concerning villages has placed villages at the forefront of development and improvement of community welfare. Villages have been given adequate authority and availability of Village Funds, so that it can manage the village’s potential, solve problems, economic growth, and improve welfare in the village. Researchers will measure changes in expenditu re per capita of the population before and after the implementation of the Village Fund program by conducting statistical analysis on secondary data from 432 districts as a research sample. From the results of analysis using regression panel data, it shows that the intervention of the Village Fund has a positive influence on the increase in expenditure per capita of the rural population. In addition, this study also found that the magnitude of the influence of the Village Fund intervention on per capita expenditure varies by region type. First, an increase in per capita expenditure was found to be grater with better village infrastructure conditions compared to areas with poor village infrastructure. Second, same pattern was also found in regions with low poverty rates compared to regions with high poverty rates. Expenditures per capita rates found higher in regions with low poverty rates compared to regions with high poverty rates.